Social media and relationship development: The effect of valence and intimacy of posts - Orben, A; Dunbar, R (Elsevier, 2017)
26% of the world’s population are monthly Facebook users (Facebook Newsroom, 2016). This development is supporting new interaction methods, some of which are neither directed nor reciprocated. For example, social media users can read online 'posts' (self-disclosures) of their friends without interacting with these friends. This is vastly different to traditional face-to-face communication. Our study investigated how reading online 'posts' affects relationship development. Using a longitudinal design sampling 243 participants, we focused on the effect of the posts’ valence and intimacy. We found that high intimacy posts or negative posts decreased the social attractiveness of the self-discloser. The perception of the posts and the receiver's feelings of homophily to the self-discloser mediated this relationship. Studies of offline interpersonal interaction have found similar results. In offline communication, self-disclosure perception and homophily also mediate relationship outcomes. This suggests that reading posts on social media and interacting in real life triggers similar or identical relationship formation pathways. These results support the argument that passive consumption is a new method of interaction that does not fundamentally change human psychology. While novel, passive consumption is still based on the same principles as offline communication.